2000
DOI: 10.1182/blood.v96.6.2037.h8002037_2037_2044
|View full text |Cite
|
Sign up to set email alerts
|

Solitary plasmacytoma of bone and asymptomatic multiple myeloma

Abstract: Most patients with multiple myeloma (MM) present with symptoms, have evidence of generalized disease, and require chemotherapy promptly to reduce the malignant clone. Some patients present with a local symptom from a single plasmacytoma but no myeloma elsewhere. Such patients usually become free of symptoms after local radiotherapy. In patients with MM without symptoms, the diagnosis is made on the basis of screening laboratory tests. In patients with either solitary plasmacytoma of bone or asymptomatic MM, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
78
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 65 publications
4
78
0
1
Order By: Relevance
“…Despite the stringent criteria employed in our study, the time to progression was similar (median of about 3 years) to that observed in other studies that included patients with a lower tumour burden (Alexanian et al, 1988, Wisloff et al, 1991, Hjorth et al, 1993, Dimopoulos et al, 1993, 2000, Facon et al, 1995, Weber et al, 1997. In our series, the only significant predictor for an earlier progression was the type of SMM (evolving versus non-evolving).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Despite the stringent criteria employed in our study, the time to progression was similar (median of about 3 years) to that observed in other studies that included patients with a lower tumour burden (Alexanian et al, 1988, Wisloff et al, 1991, Hjorth et al, 1993, Dimopoulos et al, 1993, 2000, Facon et al, 1995, Weber et al, 1997. In our series, the only significant predictor for an earlier progression was the type of SMM (evolving versus non-evolving).…”
Section: Discussionsupporting
confidence: 84%
“…This is in contrast with the findings of Wisloff et al (1991) who found that six and three of their 71 patients developed renal insufficiency or neurological symptoms respectively, at the time of progression. In the remaining series, the pattern of progression consisted of increasing bone disease, increasing M-protein or development of anaemia, with only occasional cases developing renal failure or hypercalcaemia (Alexanian et al, 1988, Hjorth et al, 1993, Dimopoulos et al, 1993, 2000, Facon et al, 1995, Weber et al, 1997. The fact that SMM patients do not develop renal insufficiency during the asymptomatic phase or at progression indicates the lack of nephrotoxic potential of their light chains.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations